2022
DOI: 10.1108/apjml-09-2021-0707
|View full text |Cite
|
Sign up to set email alerts
|

Understanding customers’ stickiness of live streaming commerce platforms: an empirical study based on modified e-commerce system success model

Abstract: PurposeLive streaming commerce enhances shopping experience and reduces uncertainty. However, with increasingly fierce competitions, it has become a challenging task for live streaming commerce platforms to retain existing customers. The purpose of this study to explore factors affecting customers’ stickiness intention toward live streaming commerce platforms.Design/methodology/approachA research model was developed by modifying e-commerce system success model (ES success model) based on the context of live st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 72 publications
(148 reference statements)
0
31
1
Order By: Relevance
“…Finally, real-time interaction can also arouse the desire of consumers to participate, so that the audience can have a full range of sensory feelings, free from time and place constraints, and enhance the audience’s sense of control and substitution for live activities ( Kim et al, 2021 ). Bao and Zhu (2022) believe that real-time interactivity is the premise factor of perceived value and customer satisfaction of live stream business platform, and then affects customers’ sticky willingness. Some scholars believe that interactive marketing stimulates the interaction between consumers and brands to increase consumers’ social value and generate impulsive consumption intention ( Souki et al, 2022 ).…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…Finally, real-time interaction can also arouse the desire of consumers to participate, so that the audience can have a full range of sensory feelings, free from time and place constraints, and enhance the audience’s sense of control and substitution for live activities ( Kim et al, 2021 ). Bao and Zhu (2022) believe that real-time interactivity is the premise factor of perceived value and customer satisfaction of live stream business platform, and then affects customers’ sticky willingness. Some scholars believe that interactive marketing stimulates the interaction between consumers and brands to increase consumers’ social value and generate impulsive consumption intention ( Souki et al, 2022 ).…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…More businesses are adopting live streaming commerce as a new marketing channel to promote sales (Bao and Zhu, 2023), launch new products (Wongkitrungrueng and Assarut, 2020) and enhance brand awareness (Kang et al. , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Live streaming commerce, combining multiple media forms with e-commerce (Bao and Zhu, 2023), involves a broadcaster (or several broadcasters) who sets up a video stream and communicates with viewers in a virtual showroom (Lin et al, 2021). Marketing activities occurring on a live streaming platform constitute a new marketing channel .…”
Section: Literature Review 21 Live Streaming Commercementioning
confidence: 99%
See 1 more Smart Citation
“…Compared to traditional e-commerce, live streaming has significant advantages in product presentation, social connection and experience enhancement (Clement Addo et al ., 2021; Zhou et al ., 2022). For instance, live streaming sellers can present products and interact with potential buyers via video, and consumers can post their comments in real time (Sun et al ., 2020; Bao and Zhu, 2022). The existing research has explored specific cues in live streaming and found their added value.…”
Section: Introductionmentioning
confidence: 99%